Acute, recurrent and repeat respiratory infections in children: the issues of immunoprophylaxis and immunotherapy - A.L. Zaplatnikov; A.A. Garina; E.I. Burtseva; Lepiseva I.V; I.D. Maikova; V.I. Svinitskaya; M.V. Leshik; N.V. Koroid; N.F. Dubovets (LCC «Medicine-Inform», 2023)
A.L. Zaplatnikov1, A.A. Girina2, E.I. Burtseva3, I.V. Lepiseva4, I.D. Maykova5, V.I. Svintsitskaya1, M.V. Leshik1, N.V. Koroid5, N.F. Dubovets5 1Russian Medical Academy of Continuous Professional Education, Moscow Russian Federation 2Khanty-Mansiysk State Medical Academy, Khanty-Mansiysk, Russian Federation 3D.I. Ivanovsky Institute of Virology, N.F. Gamaleya National Research Center of Epidemiology and Microbiology, Moscow, Russian Federation 4Children's Republican Hospital, Petrozavodsk, Russian Federation 5Z.A. Bashlyaeva Children's City Clinical Hospital, Moscow, Russian Federation The article is focused on the issues of immunoprophylaxis and immunotherapy of acute, recurrent and repeat respiratory infections in children. The authors underscore the high efficacy of active specific immunoprophylaxis against influenza virus, pneumococcal and Hib-infections. They emphasize that the use of combined immunoprophylaxis (vaccine + non-specific immunoprophylactic agents) is effective for achieving the maximal preventive effect, especially in children with recurrent and repeat respiratory infections. The article elucidates such issues as the mode of action and the efficacy of therapy and prevention, as well as the tolerability and safety of topical bacterial lysates in pediatric practice. It also reviews the pathogenetic rationale of using topical bacterial lysate IRS 19 in the prevention and treatment of acute, recurrent and repeat respiratory infections in children. The authors highlight the beneficial therapeutic effects of topical bacterial lysate Imudon on the clinical course of infectious and inflammatory oropharyngeal diseases and its preventive action. The authors outline the good tolerability of topical bacterial lysates used in pediatric practice. Taking into consideration that achievement of the most effective prevention of acute respiratory infections (ARI) in children with recurrent and repeat respiratory infections is possible via combination of immunizations, whereas topical bacterial lysates can be applied successfully as non-specific immunoprophylactic agents. Keywords: vaccination, influenza, children, immunity, immunotherapy, immunoprophylaxis, acute respiratory infections, recurrent respiratory infections, repeat respiratory infections, topical bacterial lysates, trained immunity, frequently ill children. For citation: Zaplatnikov A.L., Girina A.A., Burtseva E.I. et al. Acute, recurrent and repeat respiratory infections in children: the issues of immunoprophylaxis and immunotherapy. Russian Journal of Woman and Child Health. 2023;6(1):50-59 (in Russ.). DOI: 10.32364/2618-8430-2023-6-1-50-59.